Instrument Development of Design Thinking Test for Graphic Design Students - Asidigisianti Surya Patria; Ekohariadi Ekohariadi; Any Sutiadiningsih; Nova Kristiana; Kususanto Ditto Prihadi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Design thinking is one of the methods used to carry out the design process. So, in solving this design problem, design students, especially Graphic Design students, should carry out the stages of design thinking for the work design process. The measurement of design thinking ability is a written exam to get a standardized assessment. This Research aims to describe the development of a design thinking test instrument for graphic design students. Method: The design thinking test instrument consists of 30 multiple-choice questions. After the questions were completed, five experts validated the question. The results of content validation to five experts were analyzed using the Content Validity Ratio. The question was then tested on 30 Unesa Graphic Design students. The results of each question item were tested for validity through the Rasch model with the STATA Program and ConQuest. Results: To test the reliability of the instrument using Cronbach Alpha. The result is CVR scoring between 0.500 and 1.000, and the alpha Reliability value exceeds 0.881. The results of the total item correlation test vary from -0.0391 to 0.465, while the INFIT MNSQ value of the Rasch model starts with a value of 0.500 to 1.300. Novelty: It is concluded that the written test assessment instrument is empirically valid, so the design thinking skills assessment instrument is feasible to use.